PROBABILITY OF COVID-19 IN ABO BLOOD TYPE DURING SECOND WAVE IN SOUTHERN RAJASTHAN, INDIA - SHARMA, NEHA; TAKODARA, SOHIL; KUSHWAHA, APARAJITA; RAM, RAJU; JAT, BADRI LAL; MUKHERJEE, SANGHAPRIYA; SHARMA, ASHISH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Along the course human history of scientific research, the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is the most concerning global health problem. Second wave of COVID-19 has adversely affected India. However, India embarked on its immunization program on January 16, 2021, operating 3006 vaccination centers onset Covaxin and CoviShield. This study aimed to ascertain if there is an association amidst ABO blood type and probability of COVID-19 infection in wave. Methods: This is analytical and observational study conducted on 713 SARS-COVID-19-positive patients of a known ABO blood type, who attended outpatient department and inpatient department during March 26–May 20, 2021, in tertiary care hospital Udaipur (Raj.) Serum inflammatory markers were evaluated by Cobas 6000. Results: Out of the 713 patients who were tested positive, 15.56% was blood group Type A, 19.91% was blood group Type B, 13.65% was blood group Type AB, and 46.28% was blood group Type O. On statistical analysis, there were positive association between O+ blood type and peak inflammatory marker (interleukin-6 and D-Dimer). Patients with blood Type O who received a test were more likely to test positive and blood Type B+, A+, A+,AB+,O-,A-,B-, and AB- were less likely to test positive. Conclusion: The present study shows an evidence for interrelation between ABO blood groups and SARS-COVID-19. Reported infection prevalence is moderately increased among O+ blood type individuals. Determination of level of inflammatory markers might prove to be helpful to clinicians so as to keep track of severity of infection and evaluate the prognosis of SARS-COVID-19 with specific ABO blood groups.